Ectopic Duodenal Varices as a Rare Cause of Bleeding - Estrella, Mara Luz Terán; Quintero, Carlos Javier Mata; Sánchez, Jorge Adrián Romero; Zavala, Ana Merced Ruiz (British Journal of Healthcare and Medical Research, 2025)
Ectopic varices are dilated veins resulting from portosystemic venous collaterals that appear anywhere in the gastrointestinal mucosa except the gastroesophageal region. Gastrointestinal bleeding caused by this type of varices accounts for 5% of all variceal hemorrhages, making it an unusual cause with a high mortality rate. The optimal treatment for gastrointestinal bleeding due to ectopic duodenal varices has not been well established because of its rarity. Various treatment options have been analyzed for cases with active bleeding, with endoscopic treatment in its various modalities being the preferred choice for achieving initial hemostasis. Additionally, endoscopic treatment can be complemented with therapy guided by interventional radiology, which helps reduce the rate of rebleeding.